Envoy: Don't limit ties to diplomatic segment - Daily Express, (KK) (Daily Express (KK), 2014)
SINTOK: Relationship between Malaysia and Indonesia must not be limited to diplomatic and bilateral segments alone but rather expanded to other areas said Indonesian Ambassador to Malaysia, Herman Prayitno.